Sustainability transitions in the Global South: a multi-level perspective on urban service delivery - Lucy Oates (Taylor & Francis Group, 2021)
Urban sustainability in low and middle income countries is rarely studied from a sustainability transitions perspective, though 90% of projected population growth between 2018 and 2050 will be in cities of the Global South. Using principles from grounded theory, this paper explores the relevance of the multi-level perspective (MLP) – a prevalent analytical framework in sustainability transitions theory that has primarily been applied in the Global North – for the study of infrastructure in the Global South. It draws on empirical data collected through case study research in the cities of Ahmedabad, India, and Jinja, Uganda, which have adopted innovative socio-technical approaches to service delivery that respond to the challenges presented by urbanization, climate change and inequality. Applying the MLP to these cases shows how niche innovations by non-state actors in waste management (Ahmedabad) and solar energy (Jinja) can increase access to services, reduce ecological footprints and empower socially excluded groups, in spite (or because) of landscape pressures such as poverty, informality and limited institutional capacity. The observed benefits are attributable not only to technological but also to organizational innovation. These findings may help to develop a more flexible understanding of the types of urban transitions needed and the ways in which those transitions could be achieved. Lessons from alternative socio-technical configurations in the South could be informative for any city looking for service delivery models that better serve contemporary environmental and societal needs.